1986
DOI: 10.2337/diab.35.10.1073
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin South Florida: New Variant With Normal Electrophoretic Pattern Mistaken for Glycosylated Hemoglobin

Abstract: An 8.75-yr-old Caucasian boy was discovered to have a markedly elevated (14.8%) hemoglobin A1c (HbA1c) as estimated by ion-exchange chromatography (Bio Rex 70). Glycohemoglobin (GHb) measured by a colorimetric method with thiobarbituric acid (TBA) was normal (equivalent to a 6.4% HbA1c). Nondiabetic quantities of GHb were found with affinity chromatography, and the glucose tolerance test was normal. Intensive efforts to identify an abnormal variant hemoglobin by several electrophoretic methods were unsuccessfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 4 publications
(4 reference statements)
0
12
1
Order By: Relevance
“…He presented with symptoms of poor weight gain, polyuria, a normal glucose tolerance test, a normal Hb electrophoresis (cellulose acetate method) and HbA1c of 14.8% (ionexchange chromatography) [2,9]. Despite the normal electrophoresis results, there was a suspicion for an Hb variant due to elevated HbA1c levels in the absence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…He presented with symptoms of poor weight gain, polyuria, a normal glucose tolerance test, a normal Hb electrophoresis (cellulose acetate method) and HbA1c of 14.8% (ionexchange chromatography) [2,9]. Despite the normal electrophoresis results, there was a suspicion for an Hb variant due to elevated HbA1c levels in the absence of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…2015;6(5):229-231 electrophoresis was performed due to suspicion for a hemoglobinopathy. The results showed that the patient was heterozygous for a rare Hb variant called Hb-SF that causes falsely elevated HbA1c levels [2]. Her corrected HbA1c, when evaluated by affinity column HPLC showed results in the normoglycemic range ( Table 2).…”
Section: Case Reportmentioning
confidence: 98%
See 2 more Smart Citations
“…Occasionally, genetic variants of hemoglobin, originated by the point mutation in the globin gene, coelute with HbA 1c , which leads to overestimation of the glycemic index and subsequently wrong diagnosis of diabetes mellitus [2]. Post-translational modifications, such as acetylation of a few hemoglobin variants, have also been reported to result in coelution with HbA 1c [4,5]. Examples include Hb Raleigh, Hb Graz, Hb South Florida, Hb Sherwood Forest, and Hb Niigata [2].…”
mentioning
confidence: 99%